Novel Hydrazono‐2‐Iminothiazolidin‐4‐Ones Based on a Monoterpenic Skeleton as Potential Antitumor Agents: Synthesis, DFT Studies, in Vitro Cytotoxicity, Apoptosis Inducing Properties and Molecular Docking. Issue 7 (5th July 2022) - Fawzi, Mourad; Oubella, Ali; El Mansouri, Az‐Eddine; Bimoussa, Abdoullah; Ketatni, El Mostafa; Saadi, Mohamed; El Ammari, Lahcen; Ait Itto, Moulay Youssef; Morjani, Hamid; Auhmani, Aziz
Abstract: A series of novel 2‐iminothiazolidin‐4‐one analogs have been synthesized from limonaketone, and structurally characterized by HR‐MS, 1 H‐NMR and 13 C‐NMR spectroscopy techniques, and the structure of compound 4 was elucidated by XRD. The newly synthesized products were biologically evaluated in vitro for their cytotoxic activity against human cancer cell lines HT‐1080, A549, and MCF‐7. Thiazolidinones 9 and 10 were the most active compounds in HT‐1080 cell lines (IC50 =15.85±1.75 and 16.13±1.55 μM, respectively). The apoptosis induction of the derivatives 9 and 10 were studied using annexin V staining, caspase‐3/7 activity and cell cycle analysis. Compound 10 showed the highest ability of apoptosis induction and caspase‐3/7 activation associated with S‐phase growth arrest in HT‐1080. Meanwhile, compound 9 has a moderate apoptotic effect and G0/G1‐phase arrest in the after‐mentioned cell. The molecular docking suggested that compounds 9 and 10 formed stable ligand‐caspase‐3 complexes. Besides, the presence of phenyl moiety in ligand 10 is responsible for the enhancement of the caspase‐3 activation by the apparition of two additional hydrogen bonds with Cys163 and Gln161amino acids. Abstract :